French Orientalism and Soft (Disguised) Hegemony Roots and Extensions - Boudjemaa addad (Pegem Journal of Education and Instruction, 2026)
The duality of “knowledge and power” is a project that the French Orientalist school has consistentlypursued as a knowledge institution with an expansionist background, embodying what is known as “disguised hegemony,” as a symbolic tool that conceals intentions